Building Synergy Between Islamic Educators and National Education in Indonesia - Rusliana; St. Nurhayati Ali; Janawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Education is one of the important aspects in building a quality generation. In Indonesia, there are two education systems that run in parallel, namely Islamic Education and National Education. Both have the same goal, which is to produce individuals who are intelligent, have noble character, and are beneficial to society. However, there are still challenges in creating effective synergy between the two. This journal aims to discuss how to build synergy between Islamic Education and National Education in Indonesia in order to support the development of quality human resources. Through a study of various education policies and examples of existing implementations, it is hoped that solutions can be found to unite the two education systems without overriding the values contained in each system. It is hoped that with this synergy, Indonesia can produce a generation that is not only academically intelligent, but also has good morals and is able to face global challenges. integrating two existing education systems, namely Islamic education based on religious values and national education that focuses on character formation and skills according to the needs of the nation. In this study, it conducts a review, analysis, and synthesis of previously published works, such as books, journal articles, theses, and dissertations. The method used in this research journal uses a qualitative research method with the type of library research.